Pengaruh Pemberian Mol (Mikroorganisme Lokal) Bonggol Pisang terhadap Pertumbuhan dan Hasil Tanaman Melon (Cucumis melo. L) - Ambrosius Naitili; Asep Ikhsan Gumelar (Fakultas Pertanian, Universitas Timor, 2023)
This study aimed to (i) determine the type of concentration and frequency MOL banana weevil on the growth and yield of melon plants, (ii) to determine the response of melon plants to the use MOL (banana weevil). This research was carried out in June-August 2021, on the land of farmers in mamsena, west Insana sub-district, Regency North Central Timor (TTU). with an altitude of 600 meters above sea levels, rainfall between 2500-4000 mm. the design used in the study was a factorial randomized block design (RAK) consisting of 2 factors with 3 replication, the first factor (K) concentration consisting of (control )g, (K1) 500 ml, (K2) 1000 ml, the second factor (F) frequency of fertilization which consists of: F1 which is 2 times fertilization at planting time (WT) and 14 DAP, F2 is 3 times fertilization at planting time (WT), 14, 28 DAP, F3 fertilizing 4 times: planting time (WT), 14,28,and 42 DAP. Of these two factors, there were 9 treatment combinations, namely K0F1, K1F1, K2F1, K0F2, K1F2, K2F2, K0F3, K1F3, K2F3, so there were 27 experimental units. The result showed (i) the treatment of banan weevil MOL concentration and the frequency of watering had a significant effect on the growth and yield of melon plants. This could be seen from the interaction on the growth parameters, namely plants height 14 DAP, 28 DAP and stem diameter 14 DAP, concentration treatment MOL banana weevil 1000 ml is the best treatment in increasing the growth and yield of melon plantes. This can be seen with the highest values in the parameters of stem diameter, number of leaves, fresh weight fruit per plant, fruith length, fruit diameter, total fresh weight, leaf weight, root weight and harvest index, Treatment frequency of watering 3 times is the best treatment in increasing the growth and yield of melon plants. This can be seen with the highest values for the parameters of stem diameter, number of leaves, fresh weight of fruit per plant, fruit length, diameter of fruit, total fresh weight, and harvest index.